A study of artificial intelligence and its role in human resource management - Gaddihalli Jayaraj; Shaikh Arif; Harti Rashmi (ITM Web of Conferences)
In this present scenario requests for the human assets as an obligatory resource in arrange to progress the organizational execution. The organizations need to endeavour for embracing the imaginative HR hones to move forward their execution and be diverse in the competition. In close future, HRM is moving from the conventional way of HR hones to more advance like computerization, increased insights, mechanical autonomy and AI. Artificial intelligence is already proving to change our lives. From mechanization of ordinary and time-consuming assignments, to the expansion and enhancement of human capabilities, Computer based program has changed the way work. This may not be a fair time for HR, but it can be a dangerous time that needs to be reformed and supported. Today’s HR professionals both human and technology work to create a simple and intuitive workplace. performance.